Biodiversity discovery program Bush Blitz yields a new species of goblin spider, Cavisternum attenboroughi (Araneae: Oonopidae), from the Northern Territory - Baehr, Barbara C.; Raven, Robert; Whyte, Robert (Zootaxa, 2013)
This paper is part of the “Goblin Spider PBI” project, a world-wide revision of the spider family Oonopidae (http:// research.amnh.org/oonopidae). Oonopidae is one of the world’s most diverse spider families with over 1000 described species in 88 genera (Platnick 2012). Mostly six-eyed and tiny (1–3 mm), they are not often noticed by people because of their small size and secretive lifestyle. Most have a body shield of abdominal scutae (hardened plates). The Oonopidae are most diverse in tropical and subtropical regions (Platnick and Dupérré 2010), yet they also occur in other locations such as at high altitudes in the Himalayan Mountains (Baehr and Ubick 2010).